Use of Visual Decision Aids in Physician–Patient Communication: A Pilot Investigation. (September 2018) - Mercer, Mary Beth; Rose, Susannah L; Talerico, Cassandra; Wells, Brian J; Manne, Mahesh; Vakharia, Nirav; Jolly, Stacey; Milinovich, Alex; Bauman, Janine; Kattan, Michael W
Introduction: A risk calculator paired with a personalized decision aid (RC&DA) may foster shared decision-making in primary care. We assessed the feasibility of using an RC&DA with patients in a primary care outpatient clinic and patients' experiences regarding communication and decision-making. Methods: This pilot study was conducted with 15 patients of 3 primary care physicians at a clinic within a tertiary medical center. An atherosclerotic cardiovascular disease (ASCVD) risk calculator was used to generate a personalized RC&DA that displayed absolute 10-year risk information as an icon array graphic. Patient perceptions of utility of the RC&DA, preferences for decision-making, and uncertainty with risk reduction decisions were measured with a semi-structured interview. Results: Patients reported that the RC&DA was easy to understand and knowledge gained was useful to modify their ASCVD risk. Patients used the RC&DA to make decisions and reported low uncertainty with those decisions. Conclusions: Our findings demonstrate the feasibility of, and positive patient experiences related to using, an RC&DA to facilitate shared decision-making between physicians and patients in an outpatient primary care setting.